Penyelesaian Sengketa Lagu atau Musik di Luar Pengadilan (Lex Jurnalica, 2014)
AbstractDispute settlement rights to songs or music preferences much done outside the judicial body. The warring parties, as inventor , singer or music producer , you do not want a feud going on between them until the policy office or the Court. They seek to avoid wherever possible settlement of the dispute by such means . They are trying to avoid judicial body briokrasi rambling , impound lot of time, energy and cost . This attitude, attitudes and behaviors related to cultural mentioned law. To the East , such as Korean , Japanese and Chinese ,